Pengaruh Kefir Susu Kambing Terfortifikasi Vitamin D3 terhadap Kadar hs-CRP Tikus Rattus Norvegicus DM Tipe 2: Studi Eksperimental: The Effect of Vitamin D3-Fortified Goat Milk Kefir on hs-CRP Levels of Type 2 Diabetic Rattus Norvegicus Rats: An Experimental Study - Zulfa, Fairuz; Utomo, Astika Widy; Ardiaria, Martha; Syauqy, Ahmad; Purwanti, Rachma; Ernalia, Yanti; Masha, Tania; Maharani, Mutiara Irma; Faradina, Amelia; Panunggal, Binar (Amerta Nutrition, 2025)
Background: Insulin resistance and chronic hyperglycemia in diabetes are linked to the synthesis of the inflammatory biomarker hs-CRP. Goat milk kefir and vitamin D have anti-diabetic and anti-inflammatory properties. Objectives: Aimed to evaluate the impact of goat milk kefir fortified with vitamin D3 on hs-CRP levels of diabetic rats. Methods: Twenty-one male Rattus norvegicus rats were randomly divided into four groups for a 35-day study: Control (C), Diabetes Mellitus (DM), unfortified goat milk kefir treatment (P1), and vitamin D3-enriched goat milk kefir treatment (P2). Diabetes was induced via intraperitoneal injection of streptozotocin (STZ) at 65 mg/kg BW and nicotinamide (NA) at 230 mg/kg BW. Goat milk kefir was administered orally at 2 mL/200 g BW/day, with the fortified version containing 600 IU of vitamin D3 per 100 mL. Fasting blood glucose levels and serum hs-CRP were measured pre- and post-intervention using the GOD-PAP and ELISA methods, respectively. Data were analyzed using bivariate and multivariate methods in GraphPad Prism 8. Results: There was a statistically insignificant decrease in hs-CRP levels in the P2 group (p-value=0.21) and in the P1 group (p-value=0.63), suggesting limited impact on inflammation. However, there was a statistically significant drop in blood glucose levels in the P2 group (∆FBG -65.50±35.44 mg/dL, p-value=0.03) and in the P1 group (∆FBG -81.63±50.07 mg/dL, p-value=0.05). Conclusions: The reduction in hs-CRP levels indicates that vitamin D3-fortified kefir may help modulate low-grade inflammation and shows promise in managing diabetes. Future research should examine dose, duration, and sample size for better efficacy assessment.